2019
DOI: 10.1111/bdi.12771
|View full text |Cite
|
Sign up to set email alerts
|

Mood episodes are associated with increased cortical thinning: A longitudinal study of bipolar disorder type II

Abstract: | INTRODUC TI ONBipolar disorder (BD) is a chronic psychiatric illness characterized by episodic disturbances in mood and activity levels and affects 2%-3% of the population worldwide. 1 BD type I is defined by at least one manic episode, while BD type II is characterized by alternating episodes of hypomania and depression. The clinical significance of both subtypes is comparable in terms of illness burden, role impairments, AbstractObjectives: Previous studies found evidence for thinner frontotemporal cortice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 53 publications
3
30
0
Order By: Relevance
“…Participants had widespread bilateral cortical thinning from baseline to follow‐up ( p FWER < .05; Figure 2a–c; see Figure S2 for uncorrected maps and maps with an annualized rate of cortical thickness change), and there was no significant group difference in the rate of cortical thickness change after correction for analyses across the brain. However, uncorrected results indicated that patients had a steeper rate of cortical thinning than healthy individuals in bilateral temporal and ventromedial prefrontal cortices (Figure 2d), consistent with findings from the larger sample (Zak et al, 2019).…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…Participants had widespread bilateral cortical thinning from baseline to follow‐up ( p FWER < .05; Figure 2a–c; see Figure S2 for uncorrected maps and maps with an annualized rate of cortical thickness change), and there was no significant group difference in the rate of cortical thickness change after correction for analyses across the brain. However, uncorrected results indicated that patients had a steeper rate of cortical thinning than healthy individuals in bilateral temporal and ventromedial prefrontal cortices (Figure 2d), consistent with findings from the larger sample (Zak et al, 2019).…”
Section: Resultssupporting
confidence: 87%
“…Thinning of the cerebral cortex occurs as part of healthy aging across adulthood and might be accelerated in many psychiatric disorders, including bipolar disorder (BPD) types I and II (Fjell & Walhovd, 2010;Hibar et al, 2018;Rimol et al, 2010;Schmaal et al, 2016;Zak et al, 2019). However, the precise neurobiological mechanisms underlying longitudinal cortical thickness changes and their functional implications in healthy aging and in disease development and progression remain to be clarified.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This result is similar to a longitudinal study focused on adult BD-II patients. This study observed that adult BD-II patients with more depressive number of episodes between baseline and follow-up periods had more severe thinning of the left temporal cortex than patients with fewer depressive numbers of episodes (76). Hence, our finding further supported the association between increased cortical thinning and the number of mood episodes.…”
Section: Specific Relationship Between Ct and Clinical Variables In B...supporting
confidence: 81%